ANALYSIS THE PERFORMANCE OF THE REGIONAL HEALTH INSURANCE UNIT OPERATOR OF YOGYAKARTA APPROACHED BY THE BALANCED SCORECARD - Lamlay Sarie; Achmad Fudholi; Satibi Satibi (Faculty of Pharmacy, Universitas Gadjah Mada)
Measuring performance comprehensively on Technical Implementation Unit of the Regional Health InsuranceProvider (UPT PJKD) Yogyakarta as Administration Provider of Yogyakarta Regional Health Insurance Program(Jamkesda) with the Balanced Scorecard approach through four perspectives of customers and stakeholders, financial,internal business processes, and employees and organization capacity so that the achievement of performance havebeen made known. In this study designed non-experimental case study was descriptive. Data collected in the form of quantitativedata (questionnaire with closed questions Likert scale system of one to four, and financial statements PJKD YogyakartaUPT) and qualitative. The sampling technique used was purposive sampling. Criteria used for the respondentcustomers are not permanent teachers (GTT) I non-permanent employees (PTT) and auxiliary power (Naban) 100people, and the respondent employees consisting of officers UPTD PJKD Yogyakarta.The results showed on Customers and Stakeholders Perspective showing that the lowest value gap 5 is onthe dimensions of Responsiveness, -0,57. And the lowest perception level is on the dimensions of Empathy 3,17,this suggests that the Office of the UPT PJKD has provided satisfactory service quality for participants Jamkesda.Financial perspective suggests that the realization of UPT PJKD Yogyakarta Reimbursement in 2010 was Rp. 132 734 000, Internal Business Processes perspective suggests that: average administration service waiting time is between30-60 minutes, and the average time required to obtain reimbursement of funds is between 1 week to 1 month.Employees and Organization Capacity perspective suggests that average value Human Capital, Information Capitaldan Organization Capital officer UPTD PJKD Yogyakarta is between 60% 80% from the hope, it means a lot of officershave high performance. Key words: Analysis of the performance, Administration Provider, the Regional Health Insurance, BalancedScorecard.